Effects of Phragmites australis Shoot Remainder Silage on Growth Performance, Blood Biochemical Parameters, and Rumen Microbiota of Beef Cattle - Wang, Qiye; Zeng, Xianglin; Zeng, Yutong; Liu, Xiaoruowei; Wang, Yancan; Wang, Xin; Li, Jianzhong; Wang, Yiqiang; Feng, Zhi; Huang, Pengfei; Yin, Jia; Huang, Jing; et al. (Frontiers in Veterinary Science, 2022)
The objective of the present study was to assess the effects of replacing corn silage with Phragmites australis shoots remainder (PSR) silage on intake, growth performance, serum biochemical parameters and rumen microbial diversity of growing-finishing beef. Fifteen Angus beef cattle with an average body weight of 253±2.94kg were randomly divided into three groups (5 replicas vs each group vs Angus beef cattle). The three treatments were: group A fed 60% PSR silage +40% concentrate, group B fed 30% PSR silage +30% corn silage +40% concentrate and group C fed 60% corn silage +40% concentrate. The adaptation period was fifteen days, and the trial period lasted for 45 days. Results showed that the ADG was significantly higher and FCR was significantly lower both in groups A and B compared to group C. The results of serum biochemical parameters showed that the concentration of GLU was significantly lower in group B than both groups A and C. Microbial diversity results showed that the OTUs, Shannon, Chao1 and ACE indices were significantly lower in group A compared to groups B and C; At the phyla level, the relative abundances of Tenericutes and Melainabacteria had significant differences among three groups, the relative abundances of Papillibacter, Anaeroplasma and Anaerovorax had significant differences among three groups at the genus level; Additionally, Rikenellaceae was the uniquely biomarker among three groups. Furthermore, the results of function prediction showed that the genes families associated with metabolism of cofactors and vitamins, cellular processes and signaling, metabolism, biosynthesis of other secondary metabolites, infectious diseases, signaling molecules and interaction, nervous system and digestive system were significantly decreased, while lipid metabolism were dramatically increased from group A to C at KEGG level 2; At KEGG level 3, eleven metabolic pathways were significantly influenced among three groups. In summary, these findings indicated that PSR silage substituted the corn silage totally or partially improved the growth performance and altered the rumen microbial composition and diversity and the corresponding change of prediction function of rumen bacteria in Angus beef cattle.